2021
DOI: 10.48550/arxiv.2108.02309
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Charge completeness and the massless charge lattice in F-theory models of supergravity

David R. Morrison,
Washington Taylor

Abstract: We prove that, for every 6D supergravity theory that has an F-theory description, the property of charge completeness for the connected component of the gauge group (meaning that all charges in the corresponding charge lattice are realized by massive or massless states in the theory) is equivalent to a standard assumption made in F-theory for how geometry encodes the global gauge theory by means of the Mordell-Weil group of the elliptic fibration. This result also holds in 4D F-theory constructions for the par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 99 publications
(216 reference statements)
0
14
0
Order By: Relevance
“…Related to the swampland and 6D N = (1, 0) supergravity theories, very interesting aspects of charge completeness 3 were studied in a recent study by Morrison and Taylor [24]. They showed in [24] that for 6D F-theory models, the property of charge completeness 1 Reviews of the swampland criteria can be found in [4,5]. 2 Recent studies have investigated gauge groups formed in F-theory, for example [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Related to the swampland and 6D N = (1, 0) supergravity theories, very interesting aspects of charge completeness 3 were studied in a recent study by Morrison and Taylor [24]. They showed in [24] that for 6D F-theory models, the property of charge completeness 1 Reviews of the swampland criteria can be found in [4,5]. 2 Recent studies have investigated gauge groups formed in F-theory, for example [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…They showed in [24] that for 6D F-theory models, the property of charge completeness 1 Reviews of the swampland criteria can be found in [4,5]. 2 Recent studies have investigated gauge groups formed in F-theory, for example [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. 3 The notion of the charge completeness was discussed by the authors in [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field has been intensively studied since this progress, e.g., in[17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40] 2. There have been various efforts to analyze gauge groups formed in F-theory, e.g., in[45,46,47,48,49,50,51,52,53,54,55,56,57].…”
mentioning
confidence: 99%